Pregnancy in high schools and colleges. Moulting time, time to produce as subjects - Hernández Solís, Soledad (2021)
Pregnancy in young university students has unquestionable socio-cultural and psychological consequences at a high personal, educational, family, and social cost. The present study analyzes the experiences of women in the last semester of high school and pregnant university students. The methodological approach is based on a qualitative interpretative approach, through informal talks and semi-structured interviews, with 21 students, based on an interview guide. The analysis of the information, through a continuous process of analogy, contrast and delimiting, from a contextual approximation that enabled their organization into three thematic blocks: (i) Sexuality and breaking child dependency; (ii) I’m late! What if my period doesn’t come? What if I am pregnant? What am I going to do? My parents will kill me! and (iii) Pregnancy, cruise of anguish; examining their positioning in the face of the emergence of genital sexuality; pregnancy and the plot of life as a couple and family in the process of producing as subjects and its implications in building a life plan.